2019
DOI: 10.1021/acs.jpcb.9b08919
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Accurate Interfluorine Distances in Crystalline Organic Solids: A High-Frequency Magic Angle Spinning NMR Approach

Abstract: Long-range interatomic distance restraints are critical for the determination of molecular structures by NMR spectroscopy, both in solution and in the solid state. Fluorine is a powerful NMR probe in a wide variety of contexts, owing to its favorable magnetic properties, ease of incorporation into biological molecules, and ubiquitous use in synthetic organic molecules designed for diverse applications. Due to the large gyromagnetic ratio of the 100% naturally abundant 19 F isotope, interfluorine distances as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 65 publications
4
51
0
Order By: Relevance
“…19,20,25 Furthermore, homonuclear 19 recoupling experiments, such as two-dimensional (2D) radio frequency driven recoupling (RFDR) and delays alternating with nutation for tailored excitation (DANTE)-RFDR, are effective and can be used for interfluorine distance measurements, including in multispin systems. 15,18,19,24 In particular, long-range 1 H− 19 F and 19 F− 19 F interatomic distances 27 together with 19 F− 13 C contacts 13,21,28,29 are indispensable parameters 30 in structure elucidations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19,20,25 Furthermore, homonuclear 19 recoupling experiments, such as two-dimensional (2D) radio frequency driven recoupling (RFDR) and delays alternating with nutation for tailored excitation (DANTE)-RFDR, are effective and can be used for interfluorine distance measurements, including in multispin systems. 15,18,19,24 In particular, long-range 1 H− 19 F and 19 F− 19 F interatomic distances 27 together with 19 F− 13 C contacts 13,21,28,29 are indispensable parameters 30 in structure elucidations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, my emphasis is on advancing fluorine as an NMR probe, particularly for in situ NMR. We have established benchmark data using model proteins as well as strategies and methods to exploit fluorine labeling for structural work (Campos-Olivas et al 2002;Fritz et al 2019;Lu et al 2019a, b;Matei and Gronenborn 2016;Sharaf and Gronenborn 2015;Sharaf et al 2016). I am particularly excited to develop fluorine in-cell NMR .…”
Section: Contributions To Biophysicsmentioning
confidence: 99%
“…The recoupling of the homonuclear dipolar interactions with a train of π pulses every rotor period was originally introduced by Gullion and Vega (1992) and Bennett et al (1992). Since then, the homonuclear radio-frequencydriven recoupling (RFDR) sequence (Bennett et al, 1992) has been successfully applied for the qualitative and quantitative determinations of the dipolar spin correlations in materials (Saalwächter, 2013;Messinger et al, 2015;Fritz et al, 2019;Roos et al, 2018;Nishiyama et al, 2014a;Wong et al, 2020;Hellwagner et al, 2018;Pandey and Nishiyama, 2018) and biomolecular samples (Zheng et al, 2007;Tang et al, 2011;Shen et al, 2012;Pandey et al, 2014;Grohe et al, 2019;Andreas et al, 2015;Petkova et al, 2002;Aucoin et al, 2009;Zinke et al, 2018;Zhang et al, 2017;Zhou et al, 2012;Jain et al, 2017;Colvin et al, 2015;Shi et al, 2015;Daskalov et al, 2021). Sun et al (1995) showed that the RFDR pulse sequence element could also be used as a part of the SPICP experiment (Wu and Zilm, 1993) for removing the undesired effect of the chemical shift terms to zero order.…”
Section: Introductionmentioning
confidence: 99%